The study on the relationship between emotional intelligence towards job performance in Suruhanjaya Pencegahan Rasuah Malaysia Pahang / Suriani Ibrahim - Ibrahim, Suriani (Faculty of Business and Management, 2018)
This paper consist of the study on the four components of Emotional Intelligence (EI) and the relationship towards job performance in SPRM Pahang. EI might contribute to the job performance of an employees' in an organization. The objective of this study is to determine and investigate the relationship between EI and job performance. The four components are including, Self-Awareness, Self -Management, Social Awareness and Relationship Management were focus in this study. The respondent are consist of the employees in SPRM Pahang in total of 47. The result of relationship is indicates by the Pearson Correlation (r). The findings of this study show that person who have high level of EI is more likely to perform better in their job